Extracellular Vesicles in the Crosstalk of Autophagy and Apoptosis: A Role for Lipid Rafts - Agostina Longo; Valeria Manganelli; Roberta Misasi; Gloria Riitano; Tuba Rana Caglar; Elena Fasciolo; Serena Recalchi; Maurizio Sorice; Tina Garofalo (Cells)
Autophagy and apoptosis are two essential mechanisms regulating cell fate. Although distinct, their signaling pathways are closely interconnected through various crosstalk mechanisms. Lipid rafts are described to act as both physical and functional platforms during the early stages of autophagic and apoptotic processes. Only recently has a role for lipid raft-associated molecules in regulating EV biogenesis and release begun to emerge. In particular, lipids of EV membranes are essential components in conferring stability to these vesicles in different extracellular environments and/or to facilitate binding or uptake into recipient cells. In this review we highlight these aspects, focusing on the role of lipid molecules during apoptosis and secretory autophagy pathways. We describe the molecular machinery that connects autophagy and apoptosis with vesicular trafficking and lipid metabolism during the release of EVs, and how their alterations contribute to the development of various diseases, including autoimmune disorders and cancer. Overall, these findings emphasize the complexity of autophagy/apoptosis crosstalk and its key role in cellular dynamics, supporting the role of lipid rafts as new therapeutic targets.